Analisis Self Assessment System, Jumlah PKP, dan Penagihan Pajak Terhadap Penerimaan PPN - Kurnia, Kurnia; Azzahra, Nabila (Owner : Riset dan Jurnal Akuntansi, 2024)
Valuel 1Addedl 1Taxl (VAT) is one of the sources of state 1revenue derived from taxes imposed on consumption1 of goods and1 services in1 the customs area which can be taxed gradually in each production line. The non-achievement of the VAT revenue target is |influenced 1by several| factors such as the self-assessment system, the 1number of taxable entrepreneurs (PKP), and tax collection. In addition, the realization of VAT receipts was also not achieved due to the lack of optimal VAT in several KPPs, one of which occurred at KPP Pratama Cibeunying. The purpose of this study is to determine the impact of the Self-Assessment System, the number of taxable entrepreneurs (PKP), Tax Collection and Value Added Tax (VAT) Revenue both at KPP Pratama Cibeunying Bandung in 2018-2021.The sample were assessed byl descriptivel statisticall analysis,l classical assumption testing, 1multiplel  llinearl  regressionl analysis,l and 1lhypothesisl testing1 using the help of lIBM SPSSl 1 1Statisticsl 26l Software.l l Thel resultsl showed1l thatl thel self-assessmentl systeml (X1), the number of Taxable Entrepreneurs (PKP) (X2), and tax collection (X3) simultaneously had a significantl effectl onl Valuel Addedl Taxl (VAT) revenue. Meanwhile, partially, only the self-assessmentl systeml  has a significant influence with a positive direction on VAT receipts  and other variables such as the number of Taxable Entrepreneurs and tax collection1 does not have an impact on VAT  receipts.